Influence of time, temperature and humidity on the accuracy of alginate impressions. - Das, Gotam; Hussain, Muhammad Waqar; Chaturvedi, Saurabh; Naqash, Talib Amin; Ahmed, Abdul Razzaq; Rana, Muhammad Haseeb; Abdelmonem, Adel M (Journal of Ayub Medical College Abbottabad, 2021)
Background The goal of the current in vitro study was to assess the dimensional accuracy of dental impressions when stored at different times, temperature and humidity. Methods: Impressions were poured to an aluminium triangular die and three teeth placed at the three corners of the die. A total of 130 impressions were made, in which 10 were poured immediately following manufacturers' instructions and the remaining 120 specimens were divided into two groups on the basis of relative humidity during storage. Group-1: 100%, Group-2: 50% relative humidity. Impression was poured with type IV gypsum. The below points were chosen to determine the length between in each of the specimens using the traveling microscope with 10x magnifications after 24 hours of model recovery for calculating the effect of changes in storage conditions- relative humidity, temperature and delay in pouring the impressions, on dimensional accuracy. Results: Analysis of the results revealed that the casts achieved by pouring alginate impressions without delay were most accurate than the delay pouring. With the increase in temperature and time, the distance between the points increased and the casts obtained were bigger. Conclusion: Irreversible hydrocolloids should be poured immediately for optimum dimensional stability. Keywords: Dental impressions; irreversible hydrocolloid; dimensional accuracy